PENGARUH KONTEN FOOD VLOGGER CHANNEL YOUTUBE FARIDA NURHAN TERHADAP MINAT BERWISATA KULINER - Kiagun, Egi Sokia; Widiasanty, Gita (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
In today's digital world, technological progress is becoming increasingly evident. Now technology is freely accessible to everyone thanks to its developments. One of them is the innovation of correspondence by utilizing internet access. With the presence of the internet, the social media YouTube emerged, one of its uses is to disseminate useful information to its users, including information about culinary places. This research aims to find out whether there is an influence of Farida Nurhan's Food Vlogger Channel content on interest in culinary tourism and how much influence Farida Nurhan's YouTube channel food vlogger content has on interest in culinary tourism. The Uses and Effect theory was used as the main basis for this research. The method used in this research is a descriptive survey method using a quantitative approach. Sampling was carried out by applying incidental sampling techniques with non-probability sampling techniques. The results of this research show that there is an influence of Farida Nurhan's Youtube Channel Food Vlogger Content on Interest in Culinary Travel with a percentage of 70.9%. Meanwhile, the other 29.1% is influenced by other variables.